First-in-man experience with ultrasound renal denervation for treatment of recurrent ventricular arrhythmias. (25th November 2020) - Millenaar, D.N; Mahfoud, F; Pavlicek, V; Lauder, L; Boehm, M; Ukena, C
Abstract: Background/Introduction: Ventricular arrhythmias (VA) are common in patients with chronic heart failure (CHF) and can be refractory to drugs and catheter ablation. Promising results of sympathomodulatory treatment have been reported in these patients. Purpose: This first in man study aims at investigating catheter-based renal denervation (RDN) using ultrasound energy for treatment of refractory VA in patients with CHF. Methods: Four patients (age 65±10 years, all male, left ventricular ejection fraction 36±7%, global longitudinal strain (GLS) −10±3%) with CHF (n=1 ischemic cardiomyopathy, n=3 non-ischemic cardiomyopathy) and refractory VA were treated with RDN using ultrasound energy. All patients had undergone endo- or epicardial catheter ablation for recurrent ventricular tachycardia (VT) or fibrillation (VF) in the past and were on at least 2 antiarrhythmic drugs. Computer tomography angiography was performed at baseline, duplex ultrasound of renal arteries, ambulatory blood pressure monitoring (ABPM) and ICD interrogations were performed before, 1 day and 3 months post RDN. Results: Bilateral RDN using an ultrasound-based catheter were performed with at least 2 sonications in each main branch of the left and right renal artery. In this analysis, mean follow-up time was 113±12 days. All RDN procedures were performed without any complications. No renal artery stenoses during follow-up. Arrhythmic burden (measured as VT/VF episodes) within 3 months before RDN requiring ICD therapy was reduced from 3 [1.5–54.5] episodes of anti-tachycardia pacing (ATP) and 0.5 [0–1.25] adequate ICD shocks to 1 [0.75–1] episode of ATP. There were no adequate ICD shocks after 3 months. Mean 24-hour ABP before RDN was 94±8/65±9 mmHg with no change in BP following 3 months (SBP 92±1 mmHg, DBP 62±6 mmHg after 3 months). There was no change in left ventricular GLS (−10±3% before, −9±4% after RDN) or ejection fraction (36±7% before and after RDN). Conclusions: RDN using ultrasound energy in patients with CHF and refractory VA was safely performed with no changes in blood pressure and reduced the arrhythmic burden after 3 months follow-up. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): ReCor Medical Inc.